2007
DOI: 10.1038/sj.ijo.0803654
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between meal frequency and body mass index in black and white adolescent girls: more is less

Abstract: Measurements: Three-day food diaries, measured height and weight and self-reported physical activity and television viewing were obtained at annual in-person visits. Results: Over the course of the study, the percentage of girls eating 3 þ meals on all 3 days was reduced by over half (15 vs 6%). Participants who ate 3 þ meals on more days had lower BMI-for-age z-scores. Black girls, but not white girls, who ate 3 þ meals on more days were less likely to meet criteria for overweight. Conclusion: Meal frequency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
68
1
5

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(84 citation statements)
references
References 35 publications
10
68
1
5
Order By: Relevance
“…measured by parental educational level) and meal patterns (9,26) , similar to the association between parental employment and meal frequencies found here in the Jena children. In our children, the number of meals was significantly reduced when both parents were working full-time.…”
Section: Discussionsupporting
confidence: 83%
“…measured by parental educational level) and meal patterns (9,26) , similar to the association between parental employment and meal frequencies found here in the Jena children. In our children, the number of meals was significantly reduced when both parents were working full-time.…”
Section: Discussionsupporting
confidence: 83%
“…Longitudinal associations between a regular meal pattern/high meal frequency and obesity are scarce in this field, but a 10-year observational study among American adolescent girls revealed that a frequency of 31 meals/d was positively related to a lower BMI-for-age Z-score (15) . The study also revealed that the percentage of girls skipping meals increased from the age of 9 to 19 years (15) . Food habits and meal patterns, which are learned and acquired in childhood, tend to persist into later ages.…”
mentioning
confidence: 99%
“…Among others, the reason for skipping snacks is increased consumption of soft drinks and sweets. Previous research has shown how consumption of more meals per day causes lower risk of obesity [28].…”
Section: Discussionmentioning
confidence: 99%